PENINGKATAN KETRAMPILAN KELOMPOK WANITA DESA PASIE PINANG MELALUI PELATIHAN PRODUK OLAHAN IKAN PATIN - Nabila Ukhty; Yasrizal Yasrizal (Universitas Teuku Umar, 2019)
Catfish is a freshwater fish that is widely cultivated by fish farmers in Pasie Pinang Village. Utilization of fish is not yet optimal. Therefore, the purpose of this community service is to optimize the use of catfish through training in processed catfish products into healthy food. The training activities consist of three stages, namely preparation, implementation and evaluation. At the implementation stage, the material provided to participants consisted of ways of handling fish, types of processed catfish products, packaging and labeling, and determining the selling price. Pasie Pinang Village women's group was very enthusiastic in participating in the training activities. The achievements obtained from this activity include participants being able to develop catfish into products with high selling value, being able to process catfish products based on a household scale, being able to produce processed catfish independently, and being able to conduct marketing activities of processed catfish products.